Endoscopic Management of Sigmoid Volvulus in a Debilitated Population: What Relevance? - Rocha,Manuel Coelho da (2020)
Background: Colonic volvulus, mainly from the sigmoid, is a relatively common cause of intestinal obstruction, particularly in the elderly and in patients with debilitating conditions. The high morbi-mortality of emergency surgery places the endoscopic approach as the first-line treatment for the resolution of this acute obstructive condition. Objectives: To assess the importance of endoscopic treatment for the resolution of colonic volvulus in a debilitated population. Method: This is a retrospective analysis of emergency lower gastrointestinal endoscopies in patients with colonic volvulus as diagnosis, performed over a 9-year period (2009-2018), as well as population characterization and follow-up after the first exam. Results: We performed 88 procedures in 52 patients (56.4% males, median age 83 years, range 33-94). Endoscopic resolution was effective in 86.4% (76/88) of the exams, without procedure complications. Eighty-one percent of patients presented with volvulus recurrence, 50% of which occurred during the 3 months after the initial procedure. Twenty-one were submitted to surgery, 12 of which were emergency procedures after endoscopic failure as the primary treatment (5 of which had mucosal necrosis at endoscopy). There was no mortality in elective surgery. In the emergency plus necrosis group, mortality was 60% (3/5) and 14.3% (1/7) in the emergency without necrosis group. Conclusions: Despite the high recurrence of volvulus after endoscopic treatment, it seems to be an adequate and low-risk first-line therapy for sigmoid volvulus in debilitated patients, allowing improvement of surgical conditions.